2017
DOI: 10.1111/resp.13213
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics associated with slow gait speed in idiopathic pulmonary fibrosis

Abstract: 4MGS is a simple, reliable, valid and responsive tool that may detect a patient phenotype with worse exercise performance, dyspnoea, health status and prognosis index in stable IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 37 publications
(77 reference statements)
2
40
0
5
Order By: Relevance
“…On the other hand, walking ability needs a larger integration among the body systems in comparison with sit and stand up or tightening an object. Indeed, walking is a complex activity involving a variety of neural process (e.g., sensory, cortical cognitive, temporal) [ 40 , 41 ], cerebral and peripheral vascular beds [ 42 , 43 ], as well as lung [ 44 ], cardiac and muscular functions [ 45 ], to list a few. Consequently, walking ability represents the functioning of multiple organ systems instead of just one system [ 46 ], and marked disturbances in gait pattern may occur in response to cardiovascular, neurological and neuromuscular pathologies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, walking ability needs a larger integration among the body systems in comparison with sit and stand up or tightening an object. Indeed, walking is a complex activity involving a variety of neural process (e.g., sensory, cortical cognitive, temporal) [ 40 , 41 ], cerebral and peripheral vascular beds [ 42 , 43 ], as well as lung [ 44 ], cardiac and muscular functions [ 45 ], to list a few. Consequently, walking ability represents the functioning of multiple organ systems instead of just one system [ 46 ], and marked disturbances in gait pattern may occur in response to cardiovascular, neurological and neuromuscular pathologies [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interrater reliability was the most commonly reported measure using intraclass correlation coefficient (ICC). These were all moderate, good or excellent, range 0.68 [5STS (38) (27,(29)(30)34). 2 studies reported limits of agreement between 2 testing sessions for the 4MGS: these were 0.09 to -0.09 (34) and 0.135 to -0.125 (30).…”
Section: Reliability/ Repeatabilitymentioning
confidence: 94%
“…These were all moderate, good or excellent, range 0.68 [5STS (38) (27,(29)(30)34). 2 studies reported limits of agreement between 2 testing sessions for the 4MGS: these were 0.09 to -0.09 (34) and 0.135 to -0.125 (30). One study examined the limits of agreement for the peak oxygen uptake (VO 2 ) predicated from the DASI questionnaire and Chester step test with the CPET (36).…”
Section: Reliability/ Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The European IPF registry conducted an analysis that confirmed the demography, the clinical progression and the success of the antifibrotic treatment in improving survival in IPF. The progression of IPF is challenging and hard to foresee, but the slow gait speed in IPF could be a simple, reliable tool that may detect phenotypes associated with a worse clinical outcome. The efforts to better define the risk factors of IPF progression had led to the environmental analysis and a real association with air pollution and long‐term exposure to PM 10 and PM 2.5 linked to an increase of the mortality …”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%